Jewish Immigrant Foodways: Hyphenating America - Nadia Faradhillah (Universitas Gadjah Mada, 2017)
The article’s propose is understanding the position of Kosher Laws in Jewish foodways as religious and cultural signifier for Jews’ identity. Beside, this article also aims to explain the way the Jewish immigrants assimilate with American culture through their foodways. This topic is chosen because Jewish immigrants have unique position in American society in accordance to their food way. In the New Land that guarantees them freedom they struggle to keep their identity and assimilate as religious and cultural group through Jewish foodways.Qualitative method will be used in this library research on Jewish foodways archives and writings. This article will be started by introduction portraying Jews migration to the United States and their foodways that they brought along the migration.The findings of this research show that Jewish foodways divided the Jews for the difference of opinion between the Jews towards their Kosher Laws. The non-religious Jews adapt easily to the American foodways. The religious Jews found it difficult to assimilate to the American foodways, albeit they found a way to assimilate, yet still keep their obedience.Keywords: Kosher Law, Jewish American, Theory of Practice, Post-Nationalism, Foodways